2018
DOI: 10.5539/jel.v7n3p102
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Entrepreneurship Education on Career Development among Undergraduates in South-South Universities in Nigeria: Implication for Counselling

Abstract: This study investigated the perceived impact of entrepreneurship education on career development among undergraduates in south-south universities in Nigeria. To guide the study four research questions were generated and one hypothesis formulated, which was tested at 0.05 level of significance. The study employed an expost facto research design. The population of the study consists of all undergraduates in south-south universities in Nigeria. Sample size consists of 150 students who were randomly drawn and who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Ubong [6] also lamented that funding is a critical challenge in the implementation of entrepreneurship education in tertiary institutions in Nigeria. According to Akpochafo and Alika [11] research has shown that there are inadequate facilities and effective teaching and learning of entrepreneurship education in Nigerian institutions. Therefore, there is a need for the authority concern to provide enough funds at least 15 to 20 per cent of the annual national budgetary as recommended by UNESCO [15] for the proposed integration of entrepreneurial competencies into technical college programs to achieve the national policy on education for prosperous economic growth in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubong [6] also lamented that funding is a critical challenge in the implementation of entrepreneurship education in tertiary institutions in Nigeria. According to Akpochafo and Alika [11] research has shown that there are inadequate facilities and effective teaching and learning of entrepreneurship education in Nigerian institutions. Therefore, there is a need for the authority concern to provide enough funds at least 15 to 20 per cent of the annual national budgetary as recommended by UNESCO [15] for the proposed integration of entrepreneurial competencies into technical college programs to achieve the national policy on education for prosperous economic growth in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Abubakar Ibrahim Muhammad, Yusri Bin Kamin, Nur Husna Binti Abd. Wahid  competencies into technical education curriculum would produce creative and innovative students [11]. These students would remain more creative and innovative if the program is well design and implemented which in turn would definitely lead them to self-employment.…”
Section: Challenge Of Integrating Entrepreneurial Competencies Into Tmentioning
confidence: 99%
“…The scales for measuring entrepreneurial profile dimensions and ECD (Table 3), were used on previous consent from the authors Schmidt et al (2018) and Akpochafo and Alika (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Assessing the factors that influence the career choice of students is very imperative because it helps students in the Senior High Schools (SHS) to acquire the skills and knowledge to realistically plan for their future in the world of work [8]. Many students often are faced with uncertainty and stress as they make career choices [9]. Most of them are not aware of what goes into career choice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many students often are faced with uncertainty and stress as they make career choices [9]. Most of them are not aware of what goes into career choice [9].…”
Section: Introductionmentioning
confidence: 99%